2015
DOI: 10.1093/nar/gkv017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential for undesired genomic effects of the piggyBac transposon system in human cells

Abstract: Non-viral transposons have been used successfully for genetic modification of clinically relevant cells including embryonic stem, induced pluripotent stem, hematopoietic stem and primary human T cell types. However, there has been limited evaluation of undesired genomic effects when using transposons for human genome modification. The prevalence of piggyBac(PB)-like terminal repeat (TR) elements in the human genome raises concerns. We evaluated if there were undesired genomic effects of the PB transposon syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 43 publications
1
39
1
Order By: Relevance
“…For TcBuster , transposition was essentially over by the time the protein was detectable by western blot while for piggyBac , detectable protein expression overlapped with colony formation at the 12, 16 and 24 h timepoints. We previously analyzed piggyBac protein expression over the week following transfection and found protein expression slowly dropped after the 48-h peak (43). Different transposases are expected to reach this ‘point of no return’ earlier or later due to their solubility properties, providing an important factor by which we may be able to increase transposase activity in our favor for gene transfer or mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For TcBuster , transposition was essentially over by the time the protein was detectable by western blot while for piggyBac , detectable protein expression overlapped with colony formation at the 12, 16 and 24 h timepoints. We previously analyzed piggyBac protein expression over the week following transfection and found protein expression slowly dropped after the 48-h peak (43). Different transposases are expected to reach this ‘point of no return’ earlier or later due to their solubility properties, providing an important factor by which we may be able to increase transposase activity in our favor for gene transfer or mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an exogenously supplied T. ni PB transposase could mobilize some of the human PB-like transposons. This possibility was experimentally addressed by Saha et al, 27 who found that expression of the insect PB transposase did not mobilize endogenous, human PB-like sequences, and did not lead to an increase in DNA double-strand breaks in the human genome. Second, the endogenous, domesticated PGBD1-5 proteins could excise and/or remobilize a transgene flanked by the ITRs of a PB vector (Figure 1b).…”
mentioning
confidence: 99%
“…, the plasmid contains both transposase and the transposon) the probability that the transposase fragment will be integrated into the host cell genome may be increased, possibly through the actions of the host DNA repair mechanism. 6,33 To determine the incidence of plasmid backbone integration of the minimal piggyBac vector, we developed variants that contained two distinct reporter markers, mCherry in the transposon and eGFP in the transposase fragment of the plasmid. Adding these two fluorescent markers increased the size of the vectors, a change that caused a slight decrease in transfection efficiency, but this modification allowed us to discriminate between cells that had integrated the transposase fragment (the nontransposon part of the plasmid) from cells that had integrated only the (desired) transgene.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,5 Full-length piggyBac transposons contain long terminal repeats, however, and the enhancers and promoters embedded within those terminal repeats can lead to activation of host cell proto-oncogenes. Promoter activity in mammalian cells has been detected in a sequence within the 5′' terminal repeat of full-length piggyBac transposons 5,6 while other studies have demonstrated enhancer activity in the 3′-terminal domain. 7 Unfortunately, while the promoters that drive the delivered transgene can be insulated from the host genome, 8 the promoters and enhancers within the transposon's terminal repeats cannot be insulated without interfering with the ability of the transposon to integrate and express.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation